Modulation of regenerative responses by retinoic and ascorbic acids in human apical papilla cells - de Oliveira Fernandes, Lídia [UNESP]; Soares, Igor Paulino Mendes [UNESP]; Ribeiro, Rafael Antonio de Oliveira [UNESP]; Peruchi, Victória [UNESP]; Pires, Maria Luiza Barucci Araujo [UNESP]; Anselmi, Caroline [UNESP]; Leite, Maria Luisa; Costa, Carlos Alberto de Souza [UNESP]; Hebling, Josimeri [UNESP] (Elsevier, 2025)
Objective: This study investigated the bioactive effects of retinoic acid and ascorbic acid on hSCAPs in vitro. Design: Cells were obtained from human third molars (n=4) and characterized for mesenchymal stem cell markers by flow cytometry. The experimental groups: control (α-MEM); vehicle control group (α-MEM + 0.17 % DMSO); retinoic acid 0.1, 1, and 10 µM; and ascorbic acid 3, 30, and 300 µM (n=8) were tested for cell viability (alamarBlue; 1, 3, and 7 days), total collagen synthesis (Sirius Red; 1 and 7 days), mineralized matrix formation (Alizarin red; 14 days), and the regulation of gene expression related to mineralization (ALPL and DSPP), cell migration (ITGAV and CXCL12) angiogenesis (VEGFA) and collagen synthesis (COL1A1 and COL3A1; RT-qPCR) on 1 and 7 days. ACTB and GAPDH were used as reference genes. Data were analyzed by ANOVA and complementary tests at a 5 % significance level. Results: Ascorbic acid 300 µM increased viability, and retinoic acid reduced it dose-dependently. Retinoic acid 0.1 µM and ascorbic acid 30 and 300 µM increased mineralized matrix formation and total collagen synthesis, and retinoic acid 10 µM decreased. On day 1, 0.1 µM retinoic acid upregulated the gene expression of COL1A1, COL3A1, VEGFA, CXCL12, ALPL, DSPP e ITGAV, and 300 µM ascorbic acid upregulated COL1A1, COL3A1 and DSPP. However, on day 7, retinoic acid downregulated ALPL, COL3A1, CXCL12, and VEGFA and downregulated ITGAV and VEGFA. Conclusion: Retinoic acid 0.1 µM and ascorbic acid 300 µM biostimulated hSCAPs to differentiate into pro-regenerative phenotypes with potential application for REPs.
Keywords: Ascorbic acid; Dental papilla; Dental pulp; Guided tissue regeneration; Retinoic acid; Tretinoin